Energy exchange in globally coupled mechanical phase oscillators - Sosa, Raúl I.; Zanette, Damian Horacio (American Physical Society, 2020)
Fil: Sosa, Raúl Comisión Nacional de Energía Atómica. Instituto Balseiro; Universidad Nacional de Cuyo, Argentina